О’smirlik dаvridа stress xоlаtlаrining ijtimоiy psixоlоgik xususiyаtlаri (SCIENCE and SOCIETY, 2025)
The article discusses the main scientific approaches to studying the problem of stress and examines the psychological aspects of stress characteristic of adolescents. The causes of stress are analyzed. Special attention is paid to the effects of stress, such as anxiety, depression and deterioration of psychological well-being. The article also discusses methods of psychological correction of stress management and strategies that can help teenagers cope with difficulties.